PENGARUH FEAR OF MISSING OUT (FOMO), PERILAKU PEMBELIAN IMPULSIF, DAN MEDIA SOSIAL TERHADAP MINAT BELI BELANJA ONLINE PADA GENERASI Z - Mandira, Ayu; Zaerofi, Afif (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2025)
This study was conducted to determine how much influence Fear of Missing Out (Fomo), Impulsive Buying, and Social Media have on online shopping interest in generation Z. The research method uses a causal quantitative method. The population used is generation Z with a sample of 170 respondents selected using purposive sampling techniques, where data was collected through a Google Form questionnaire and distributed to generation Z. The data used was analyzed using SPSS. The result of this study indicate that (1) Fear of Missing Out (FoMO) has a positive and significant effect on online shopping interest in generation Z (2) Impulsive Buying has a negative and insignificant effect on online shopping interest in generation Z (3) Social Media has a positive and significant effect on online shopping interest in generation Z (4) Fear of Missing Out (FoMO), Impulsive Buying, and Social Media have a simultaneous effect on online shopping interest in generation Z.